Pengaruh Kualitas Produk dan Harga Terhadap Target Penjualan Pada UD. Barokah D&A Chicken Farm - dwi jayanti putri, amalia rosa (PERFORMA, 2023)
“The Effect of Product Quality and Price on Sale Target at UD. Barokah D&A Chicken Farm” The production of chicken eggs in Indonesia keeps of increasing starting from 2009 to 2019. Besides, there is positive opportunity from chicken egg business, inculding UD. Barokah D&A Chicken Farm that runs in livestock industry, which produces and sells egg in Lamongan district. However, there are problems of price and quality of existing eggs in Lamongan district with other districts that make chicken egg distributors tend to buy eggs from other disctricts, so that the sale turnover of UD. Barokah D&A Chicken Farm becomes decreased during this recent 5 years. The turnover decrease results sale target can’t be achieve based on the target that has be determine. The purpose of this research is to find out the effect of product quality on sale target, and find out the effect of price on sale target at UD. Barokah D&A Chicken Farm in Lamongan District. This research is quantitative research. To gather sample, this research uses purposive sampling technique, and to collect data process, this research uses questionnaire that is disributed to 206 respondents that consist of 115 (56%) female and 91 (44%) male. Data analysis is done using SPSS software. The result of the research shows that product quality and price have effect significantly on sale target. It means that there is similiarity between product quality and price on sale target that has been determine by UD. Barokah D&A Chicken Farm before. Therefore, it is found that the conclusion that the effect that is given by product quality and price variables on sale target is quite strong when it occurs directly without other variables that have the role as moderator or mediator. Keywords: product quality, price, sale target